The enduring effects of relational attributes on subsidiary evolution after mandate loss. (30th September 2020) - Gillmore, Edward; Andersson, Ulf; Ekman, Peter
Abstract: Research Summary: We explore the importance of the relational attributes, trust and commitment, and their association with subsidiary development after mandate loss. We examine how greenfield and acquired subsidiaries, through their interaction with headquarters and sister subsidiaries, develop relational attributes through mutual‐orientated adaption. These relational attributes are subsequently important elements in upholding and developing subsidiary activities despite the loss of a mandate. We trail this process through a longitudinal field study following the evolution of four multinational enterprise (MNE) subsidiaries. We explain how the subsidiaries relational attributes and part of their activities, associated with its mandates, remain even after the loss of a mandate. The study shows how these relational attributes mitigate and compensate for formal mandate loss. Managerial Summary: Subsidiaries have been increasingly seen as the locomotive of MNEs value creation. This has coincided with the disaggregation of the MNEs value chain which has had a positive effect on the development of foreign subsidiaries. However, there is now more competition for responsibilities among subsidiaries leading to increased movement of responsibilities and activities between them. We find that the subsidiary managers relationship attributes (trust and commitment) between them, their headquarters and other subsidiaries in the MNE has a mitigating effect on the loss of these responsibilities for the subsidiary. By showing the impact of managerial micro‐activities in the MNE, our study offers insights for subsidiary managers on what they can leverage to pursue subsidiary charter consolidating activities and survival, or charter enhancing activities and growth.